Design and feasibility of an international study assessing the prevalence of contact allergy to fragrances in the general population: the European Dermato-Epidemiology Network Fragrance Study - Rossi, Marta; Coenraads, Pieter-Jan; Diepgen, Thomas L.; Svensson, Åke; Elsner, Peter; Gonçalo, Margarida; Bruze, Magnus; Naldi, Luigi (Dermatology, 2010)
Background/Aims: Data on contact allergy to fragrances in the general population are limited. Data from allergological services suggest that the frequency of contact allergy to fragrances is increasing. The European Dermato-Epidemiology Network (EDEN) Fragrance Study aims to obtain reliable data on the prevalence of contact allergy to fragrances and other sensitizers of the European baseline series, in the general population of different geographical areas of Europe. We report the methodology and the reliability of instruments adopted and discuss the feasibility based on a pilot phase. Methods: Descriptive epidemiology survey. A random sample from the general population is selected and interviewed, and is offered patch testing in a randomized way. We specifically enquire about any skin rash reported during the previous year, and any history of reactions to products that may contain the sensitizer and/or a history of avoidance of the same products. Patch test data are linked to the questionnaire information to define clinical relevance. Results: The questionnaire showed high test-retest reliability in 94 individuals. Patch test reading also showed a high level of interrater reliability. During the pilot phase, a total of 589 participants were recruited. Conclusions: The EDEN Fragrance Study is feasible and able to provide useful data on fragrance allergy.
Gesehen am 21.06.2023